Use of lexical loans in Aymara in the Jiwasanaka program during the pandemic - Oliva Quispe, Nora Elizabeth (2025)
At the beginning of 2020, in Peru, the pandemic had a significant impact that connected aspects such as language, health, education, and information. The objective of this article is to analyze and describe the use of Aymara language borrowings in the Jiwasanaka (‘We’) program during the pandemic. It is very important to detail the role played by the Jiwasanaka (‘We’) program in providing viewers with information about the coronavirus in their native language. Methodologically, the study is qualitative and descriptive. The corpus consists of five videos or five programs that were published on YouTube in March, April, May, and June 2020. The results show that health-related loanwords during the health crisis have been integrated into the language of Aymara speakers due to communicative necessity and the lack of equivalent terms, adapting or being adapted to Aymara grammar.